Work-Life Balance and People-Oriented Management: Enhancing Employee Well-being for Sustainable Business Performance - Permatasari, Sinta Eka; Lilan, Lu; Hao, Zhang; Purwanto, Purwanto (AIBPM Publisher, 2024)
In the realm of management focusing on peopleâ€™s needs and growth also known as leadership plays a role, in enhancing both employees well-being and the overall success of a company in the long run. It involves giving priority to employees well-being and development while fostering a work environment based on trust, respect and empowerment. By adopting this approach employee performance and dedication to the organization are enhanced. A qualitative study was conducted involving HRD managers from five companies to explore the implementation of people-oriented management strategies. The results indicated that emphasizing trust, respect and empowerment within organizations through communication and engagement initiatives can create a work environment that promotes a healthy work life balance ultimately boosting employee productivity and performance. Furthermore, this approach contributes to improving employee well-being and loyalty to the organization. Therefore, embracing people centered management practices can lead to outcomes.Â Keywords: People-oriented management, employee well-being, employee performance, commitment, organizational outcomes.